THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHER DEVELOPING A CULTURE OF CARE FOR THE ENVIRONMENT AT AL-WAHAB BAGO KRADENAN VOCATIONAL SCHOOL - Rohmad, Nur; Khasanah, Uswatun (Proceeding of International Conference of Islamic Education, 2023)
The context of this research is the existence of a phenomenon where the increasingly modern era requires people to develop and advance even out of control, so that the great desire of humans to master nature is very large, but the school seeks that students do not deviate monotheism and morality, then give learning about environmentally sound Islamic religious education. This research metod SMK Al-WAHAB Bago Kradenan included in qualitative research, and the type of research is multisite, with data collection techniques, namely: In depth interviews, participant observation and documentation. While for technical data analysis using descriptive analysis which includes: Data reduction, data presentation and verification. The results of this study indicate that: (1) Implementation of environmentally sound Islamic Religious Education. a) There is a change in the vision, mission and objectives of the school. b) Subjects are integrated into environmentally friendly school programs. c) Planting Islamic environmental ethical values. (2) Culture of caring for the environment in schools. a) The development of cultural programs that care about the environment in schools. b) Collaboration with several institutions. c) Outreach socialization. (3) Learning outcomes of Islamic Education in developing a culture of caring for the environment ... a) The realization of the vision, mission, goals and motto of the school b) The influence of students' morals and character. c) The success of the institution in instilling religious values.